Respuesta :

Space

Answer:

(-2, 0)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Algebra I

  • Solving systems of equations using substitution/elimination

Step-by-step explanation:

Step 1: Define Systems

-x - 2y = 2

4x - 2y = -8

Step 2: Rewrite Systems

-x - 2y = 2

  1. Multiply both sides by -1:                    x + 2y = -2

Step 3: Redefine Systems

x + 2y = -2

4x - 2y = -8

Step 4: Solve for x

Elimination

  1. Combine equations:                    5x = -10
  2. Divide 5 on both sides:                x = -2

Step 5: Solve for y

  1. Define equation:                    4x - 2y = -8
  2. Substitute in x:                       4(-2) - 2y = -8
  3. Multiply:                                  -8 - 2y = -8
  4. Isolate y term:                        -2y = 0
  5. Isolate y:                                 y = 0

Greetings again.

The answer is (-2,0)

Explanation:

This one is different from other 2 previous questions. The last and previous 2 questions have positive y for another equation and negative y for another equation which makes them 0 (As y - y = 0)

But this one is different. y-terms both are negative for both equations. If we decide to add -2y and -2y then It'd make -4y which doesn't make 0.

And how are we gonna solve by elimination? That's simple. By multiplying one of the equation by -1.

We can do that, to eliminate y-term out. Choose one equation to multiply. I'll be multiplying -1 in the first equation.

[tex]-x-2y=2[/tex]

Multiply -1 in whole equation.

[tex]-x(-1)-2y(-1)=2(-1)\\x+2y=-2[/tex]

Remind that negative multiply/distribute in negative equal positive always.

And x + 2y = -2 is your new equation from the first equation.

[tex]\left \{ {{x+2y=-2} \atop {4x-2y=-8}} \right.[/tex]

This is our new equations. Then we are able to eliminate y-term.

[tex]5x=-10\\x=-2[/tex]

In case if you forget again, we can simply add/subtract vertically.

x+4x = 5x

2y-2y = 0

-2-8 = -10

That's how we get 5x=-10 and thus x = -2.

We already get x-value, and you know that we need to find the y-value too.

Therefore, substitute x = -2 in any given equations. Less coefficient value, the faster and better.

I'll substitute in -x-2y=2

[tex]-x-2y=2[/tex]

Substitute x = -2 in the equation.

[tex]-(-2)-2y=2\\2-2y=2\\-2y=2-2\\-2y=0\\y=\frac{0}{-2}\\y=0[/tex]

Thus, when x = -2, y = 0. Since you want the answer as ordered pair, then the answer is (-2,0)